Ответы и объяснения

Лучший Ответ!
2012-09-25T00:09:55+04:00

a)

2^(sqrtx+1)+2^(sqrtx)=3^(sqrtx-1)+3^(sqrtx)

2^sqrtx*2+2^sqrtx=3^sqrtx*1/3+3^sqrtx

2^sqrtx(2+1)=3^sqrtx(1/3+1)

2^sqrtx/3^sqrtx=4/3:3

2^sqrtx/3^sqrtx=4/9

(2/3)^sqrtx=4/9

(2/3)^sqrtx=(2/3)^2

sqrtx=2

x=4

 

б)

3^(x^2+2)-3^(x^2-1)=5^(x^2+1)+5^(x^2-1)

3^x^2*9-3^x^2*1/3=5^x^2*5+5^x^2*1/5

3^x^2(9-1/3)=5^x^2(5+1/5)

3^x^2/5^x^2=26/5:26/3

(3/5)^x^2=3/5

x^2=1

x=1

x=-1

 

 

2012-09-25T00:16:33+04:00

2^(√x)*(2¹+2⁰)=3^(√x)*(3⁻¹+3⁰);

2^(√x)*(3)=3^(√x)*(4/3);

3*2^(√x-2)=3^(√x-1);

2^(√x-2)=3^(√x-2);

√x-2=0;

√x=2;

x=4.

 

Во втором вынеси за скобки степень х²...